Hybrid Approach for Moving Object Detection in Video Surveillance System - Lavanya, PL.D.; Mahesh, Dr.K. (IJRDO -Journal of Computer Science Engineering, 2016)
Object tracking detection plays a vital role in video surveillance system. It is mainly focused in banks, tele conferencing, shopping and traffic monitor system. Object tracking is the process of detecting objects which is moving in sequences frames of a video, to detect the moving objects, different techniques are used such as background subtraction, optical flow, GMM(Gaussian Mixture Model). The main objective of the proposed work is to detect the moving objects with less complexity and accuracy using frame differencing method. First background subtraction is detected using recursive technique. Then noises are removed by wiener filter and YCbCr Color space for foreground object. In order to obtain accurate detection, shape based image retrieval technique is used. Finally the experimental results show that this method can reduce complexity and generate accurate image without any noises.